Implementation of PPKM In Social Economic Change Perspectives of Daily Labor And Workers In The New Normal Era - HR, Syamsuni; Malli, Rusli; Sumiati, Sumiati; Hasnawati, Hasnawati; Nursyam, Aisyah (Green Publisher Indonesia, 2022)
At the beginning of 2020, the world considered that the spread of Covid-19 was endemic. It is so fast that the WHO has determined that Covid-19 is a pandemic that must be watched out for. Although many countries have implemented lockdowns, the spread of Covid-19 is so fast and seems to be out of control, and viral replication is fast. Travel restrictions and patient isolation are the Indonesian government's strategies in dealing with the Covid-19 pandemic in the PPKM concept (implementation of restrictions on community activities (PPKM), implemented in every country. Observations show that daily laborers and masons are communities with low access to housing categories. 67% of daily laborers and masons live in uninhabitable houses and slum areas, 20% live for rent, the rest live in their own houses. Daily workers and masons' residence conditions are the houses on stilts, which are made of wood with a zinc roof with